Psychological effects of isolation on antenatal women during COVID-19 pandemic - Kamalakshy, Chandramathy; Chenicheri, Mini; Ratheesh, Lakshmi Chirayil; Gangadharan, Ragesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pregnancy is a time of increased vulnerability for the development of anxiety and depression. This study evaluated the psychological effect of isolation on antenatal women admitted with COVID-19 disease. Methods: A cross-sectional study conducted at Government medical college Kozhikode from 1 November 2020 to 31 January 2021. One hundred antenatal women with COVID-19 disease admitted in isolation ward in quarantine were randomly selected. Clinical and demographic data collected at the time of admission. After one week of admission, mental health assessment done using following mental health assessment tools. They were general anxiety disorder-7 (GAD-7), perinatal anxiety screening scale (PASS), patient health questionnaire-9 (PHQ-9). Results: Out of the 100 women selected, 74 responded with the questionnaires. All of them were educated, 62% studied up to plus two. Majority from joint family contributed 68.9% and 85.1% were home makers. Mean age was 26 years. Primigravidae were 48.6% and mean BMI of 25.71 kg/m2. Commonest medical comorbidity was diabetes mellitus present in 28.4%. Mental health assessment done using 3 sets of questionnaires, PHQ-9, GAD-7 and PASS showed that women in our study did not have any increased risk of depression, general anxiety or perinatal anxiety. Infact they reported of feeling safer and more comfortable at the hospital compared to home. Conclusions: Present study showed that antenatal women with COVID-19 disease admitted in hospital did not have any increased risk of general anxiety, depression or perinatal anxiety.